Enhancing Contact Tracing for Serratia marcescens Biofilm on High-Usage Body Towels in Rivers State Bathrooms - Amadi Ikpa; Ogbonda KH (Journal of Healthcare and Biomedical Science, 2023)
The placement of body towels before and after use in bathrooms where Serratia marcescens proliferates calls for concern, as Serratia marcescens, an airborne opportunistic pathogen has been reported keratinolytic.  Serratia marcescens, a bacterium commonly noticed with a pink or red slimy appearance in toilet sinks, bowls, and tiles presents an aesthetically, unappealing and disgusting appearance in the toilet surroundings. The study aimed to trace the presence of Serratia marcescens on frequently used body towels hung in the bathroom doors. Swabs from forty (40) differently used towels were collected from twenty (20) volunteered homes and analyzed using standard microbiological procedures. Microbiological procedures involved inoculating the swab sample on a prepared peptone broth and plating on MacConkey agar media, followed by identification and streak of the recovered isolate onto Congo red agar media for biofilm formation.  Results showed the recovery of Serratia marcescens isolates. The three homes showed a Serratia marcescens count of 3 X 10, 1 X 102, and 7 X 10 CFU per swab for house units C, I, and P respectively.  Serratia marcescens could form a biofilm, a basic feature that allowed it to strive on a body towel. The results derived strongly identified the presence of Serratia marcescens biofilm on body towels hung in the bathrooms. This could have health implications for towel users due to the bacteria's keratolytic properties. Hence, the need for constant surveillance to support effective measures of hygiene, aimed at preventing the spread of Serratia marcescens is recommended.